2016
DOI: 10.3390/atmos7070086
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Study on High-Resolution Numerical Modeling of Static Topographic Data

Abstract: Both research-grade and operational numerical weather prediction models perform simulations with horizontal grid spacings as fine as 1 km, and their multi-scale terrain data have become increasingly important for high-resolution model forecasting. This study focused on the influence of multi-scale surface databases of topographical height and land use on the modeling of atmospheric circulation in a megacity. The default data were the global 30S United States Geographic Survey terrain data set and Moderate Reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Previous similar studies have shown similar biases in precipitation and maximum core location [16,24,25]. To improve the model performance for the precipitation amount and core location, additional methods could be applied, such as using a finer model resolution, improved physical parameterizations, and effective initial conditions via data assimilation.…”
Section: Default Model Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous similar studies have shown similar biases in precipitation and maximum core location [16,24,25]. To improve the model performance for the precipitation amount and core location, additional methods could be applied, such as using a finer model resolution, improved physical parameterizations, and effective initial conditions via data assimilation.…”
Section: Default Model Resultsmentioning
confidence: 90%
“…The model configuration used here is the same as that described in [16] with WRF version 3.6.1 representing Seoul and its suburban cities in Korea ( Figure 1). That is, the model is configured in the Lambert conformal map projection with the central latitude of 38 • N and longitude of 126 • E. It uses a one-way nested domain configuration consisting of a 5-km resolution outer domain ( Figure 1a) and a 1-km resolution inner domain (Figure 1b), with 332 × 293 and 336 × 286 grid points, respectively.…”
Section: Model Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Precipitation forecasts and simulations of severe weather can be sensitive to cloud microphysics and cumulus parameterizations [15][16][17][18][19][20][21][22][23]. Surface variables (e.g., wind) can also be sensitive to the land surface model, land use and topography [24][25][26][27][28]. Data assimilation has an impact on atmospheric or oceanic models in general, and it also plays an important role in WRF model simulations [29]; post-processing can also improve the results [30].…”
Section: Introductionmentioning
confidence: 99%
“…Akimoto and Kusaka 2010;Carvalho, Rocha, and Gómez-Gesteira 2012;Misaki et al 2019), (b) topography and land use (e.g. Cheng et al 2013;Jee and Kim 2016;Jiménez-Esteve et al 2018;Mallard, Spero, and Taylor 2018;Kikuchi, Fukushima, and Ishihara 2020), and (c) sea surface temperature (SST) as a lower boundary condition (e.g. LaCasse et al 2008;Song et al 2009;Shimada et al 2015;Kikuchi, Fukushima, and Ishihara 2020).…”
Section: Introductionmentioning
confidence: 99%